2017
DOI: 10.1590/0103-6440201701237
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Early Childhood Caries and Associated Factors in Brazilian Children

Abstract: Early childhood caries (ECC) affects children all over the world and has high prevalence and severity in preschool children. Different social, biological and behavioral factors compose a network of causal factors for ECC. The aim was to evaluate the association between socioeconomic variables and caries at baseline, and the presence of Streptococcus mutans and Lactobacillus spp. microorganisms with the progression of caries lesions after two years of follow-up in a group of children. At baseline, 163 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
2
13
0
2
Order By: Relevance
“…There is considerable evidence that the strongest predictor of future caries among children is current caries (Attaran et al 2016), and our study confirms that children with a history of dental caries were more likely to belong to our reference category: severe caries. Similar findings were observed in longitudinal studies (Parisotto et al 2012; Piva et al 2017): one such revealed that after 2-y follow-up, the severity of baseline caries that included dentine lesions (ICDAS 4 to 6) had almost doubled (Piva et al 2017). Another study found that even past noncavitated lesions at baseline apparently increased the risk of developing new caries (Parisotto et al 2012).…”
Section: Discussionsupporting
confidence: 79%
“…There is considerable evidence that the strongest predictor of future caries among children is current caries (Attaran et al 2016), and our study confirms that children with a history of dental caries were more likely to belong to our reference category: severe caries. Similar findings were observed in longitudinal studies (Parisotto et al 2012; Piva et al 2017): one such revealed that after 2-y follow-up, the severity of baseline caries that included dentine lesions (ICDAS 4 to 6) had almost doubled (Piva et al 2017). Another study found that even past noncavitated lesions at baseline apparently increased the risk of developing new caries (Parisotto et al 2012).…”
Section: Discussionsupporting
confidence: 79%
“…A recent systematic review reports that baseline caries was the strongest predictor for future dental caries in countries with very high human development indices, similar to this Australian population . Likewise, progression of carious lesions was positively associated with baseline caries among a population of Brazilian children , and according to Brennan and Spencer, greater caries experience at age 13 was associated with more missing or filled teeth in adulthood . However, none of the above studies have explored the range of variables reported here.…”
Section: Discussionmentioning
confidence: 74%
“…Studies differed in their grouping of caries scores. For example, nine different caries surfaces measures and seven caries teeth measures were identified in this review. Some studies grouped them to classify caries as dentin and enamel lesions while others classified them as initial/early, moderate/established and severe/extensive lesions .…”
Section: Discussionmentioning
confidence: 99%